Relationship between Mastery Motivation and Sensory Processing Difficulties in South Korean Children with Developmental Coordination Disorder - Hee Young Kim (Occupational Therapy International)
The aim of this study was to identify the correlation between mastery motivation and sensory processing difficulties among South Korean children with developmental coordination disorder (DCD). Ninety-nine children aged 4–7 years with DCD participated. The Dimensions of Mastery Questionnaire was used to assess the mastery motivation of the children, and the Short Sensory Profile was used to assess the children’s sensory processing difficulties. All subjects showed lower mastery motivation and definite differences in sensory processing. Mastery motivation was significantly correlated with sensory processing (r=−0.34, p=0.01). Mastery motivation predicted 41.1% of the sensory processing. In particular, a negative reaction to failure in mastery situations scale (p<0.01) and general competence compared to peers scale (p<0.05) in mastery motivation were significant predictors. This study indicated that sensory processing difficulties and lack of mastery motivation were identified among children with DCD in South Korea. And the children with high mastery motivation show less difficulty in sensory processing. It is suggested to develop possible solution for higher mastery motivation to improve sensory processing of the children with DCD in South Korea.